Evaluation of Selective Physicochemical and Biological Properties of Different Root Canal Sealers - Borges, Alvaro Henrique; Guedes, Orlando Aguirre; Pereira, Thiago Machado; Guapo-Pavarina, Rodirgo; da Rosa, Wellington Luiz de Oliveira; Piva, Evandro (Iranian Endodontic Journal, 2019)
Introduction: This in vitro study aimed to evaluate the chemical composition, water solubility, radiopacity, pH, electrical conductivity and cytotoxicity of four different root canal sealers. Methods and Materials: Four materials were tested including an epoxy resin-based sealer (AH-Plus), a calcium silicate-based sealer (MTA Fillapex), a calcium hydroxide-based sealer (Sealapex) and a zinc-oxide-eugenol-based sealer (Endofill). The materials were submitted to energy-dispersive x-ray microanalysis for elemental chemical composition. Solubility and radiopacity were evaluated according to ANSI/ADA. The pH and electrical conductivity were measured at different periods of time. L929 immortalized mouse fibroblast line were used for cytotoxicity evaluation. Statistical analyses were carried out using the ANOVA and Tukey’s test. Results: The main elements were found to be silicon and calcium in MTA Fillapex, calcium and bismuth in Sealapex, zirconium and tungsten in AH-Plus and zinc and bismuth in Endofill. Sealapex had the highest value for solubility (P<0.05), AH-Plus showed the highest radiopacity value (P<0.05) while MTA Fillapex had the highest pH and electrical conductivity values (P<0.05). AH-Plus showed the highest rate of cell viability (P<0.05). Conclusion: Based on the results of this in vitro study, it was possible to conclude that Endofill and Sealpex did not meet the requirements for water solubility. The tested sealers were alkaline and showed radiopacity in accordance with ANSI/ADA standards. AH-Plus showed to be less cytotoxic than other tested root canal sealers. Keywords: Biological Assay; Endodontics; Root Canal Filling Materials; Root Canal Obturation